Complex regional assessment possibilities of competitiveness of the information economy and society in Hungary: from regional statistics to regional policy - Akos Jakobi (European Regional Science Association (ERSA), 2012)
Since ICT factors got growing importance in shaping social and economic differences, the determination of competitiveness in the information economy and society became needful in understanding modern regional disparities of Hungary. To evaluate recent inequalities caused by the factors of information and communication technologies (ICT) complex indices of competitiveness were created, which can reveal the reasons of major inequalities in the level of information society development. By the application of the widely known Bennett methodology estimations on the level of Hungarian small regions (NUTS4 or LAU1) were carried out based on regional statistical data. Additionally calculations were made on the three major segments of ICT competitiveness reflecting also the advantages and disadvantages of structural circumstances. The structural factors of competitiveness in the examinations were the level of information infrastructure, the level of social adaptivity of ICT innovations and the level of the information economy, each of them measured by a complex index created from each structural factor's multivariable dataset. According to the results the majority of small regions have no kind of advantage in competitiveness, while only 10% percent of the small regions in Hungary have all components of advantage: good infrastructure, high level of social adaptivity and developed information economy. By the recognition of ICT-based inequalities the strategic policy also tried to formulate suitable answers on how to develop regional information society. ICT-based regional strategies were created, which formulated several development directions and suggestions, however, they did not fully reach their aims. The efficiency of the strategies is below expected. Due to lack of allocated financial sources the strategic plans seem to be only bookshelf documents with no influences on regional inequalities. On the other hand there are also examples on successful development tools, but those have only indirect connections with regional information strategies. All in all the aim of this research paper is to describe what inequalities are present in Hungary and how they are introduced in regional plans, as well as to reveal the real possibilities of the application of this development tool by the evaluation of changes observable in statistical reports.
Keywords: L86; L96; O18; R00; R58; 330; information and communication technologies; information society; information economy; Hungary; regional disparities; regional information strategies